Papel da via S100β/RAGE/NFκB na patogênese da mucosite intestinal experimental por 5-fluorouracil: regulação de células gliais e de neurônios entéricos - Costa, Deiziane Viana da Silva (2016)
5-Fluorouracil (5-FU) promotes intestinal mucositis and motility alterations. The mucositis affect about 40% of patients receiving 5-FU and there are reports of patients presenting mucositis after the first dose. Under other inflammatory conditions, the S100β protein is involved in the RAGE activation with subsequent NFκB translocation to the nucleus and transcription of TNF-α and iNOS. The enteric glial cells through several mediators, such as S100β, interact with the intestinal epithelial cells and enteric neurons. Therefore, the aim of this study was investigate the effect of 5-FU in the enteric glial cells and neurons, as well as study the role of the via S100β/RAGE/NFκB in the pathogenesis of the experimental intestinal mucositis. Swiss male mice received saline (control, 0.9%, i.p.) or 5-FU (450 mg/Kg, i.p., single dose). After 24h, mice were treated with pentamidine, a S100β inhibitor (P0.8 mg/Kg +5FU; P4 mg/Kg +5FU; or only P4mg/Kg, i.p.) during two days and euthanized on the fouth day of the experimental protocol. The segments of the small intestine and colon were collected to analyze the following parameters: weight loss; histological alterations; expression of enteric glial cells (GFAP e S100β) and neuronal (HuC/D) marker using immunohistochemistry; expression of iNOS and co-localization of GFAP and Iba-1, and HuC/D and RAGE or NFκB NLS using immunofluorescence; protein expression of S100β, NFκB p65, iNOS and RAGE by Western Blotting; genic expression of GFAP, S100β and iNOS using qPCR; The levels of nitrite/nitrate, GSH, MDA, TNF-α and IL6 by ELISA. The 5-FU promoted reduction of intestinal villus, loss of crypts integrity, intense inflammatory cell infiltrate and hypertrophy of the myenteric plexus, as well as increased the GFAP and S100β immunostaining and diminished the HuC/D immunostaining. 5-FU was also able to elevate RAGE and NFκB NLS immunostaining in the enteric neurons and Iba-1 in the intestine, as well as, augmented the protein expression of S100β, RAGE, NFκB p65 and iNOS, and the genic expression of S100β, GFAP and iNOS. Furthermore, it enhanced the MDA, nitrite/nitrate and proinflammatory cytokines (TNF-α e IL-6) levels in the small intestine and colon. The S100β inhibition was able to revert these changes promoted by 5-FU. We provide evidence that 5-FU promote reactive gliosis, leading reduction of the enteric neurons via S100β/RAGE/NFκB. Together, these results suggest that S100β is a mediator important involved in the pathogenesis of the 5-FU-induced intestinal mucositis.